2014
DOI: 10.1097/paf.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Sudden Unexpected Death Due to a Glial Cyst of the Pineal Gland

Abstract: Pineal cysts are usually asymptomatic; however, they may rarely cause symptoms such as chronic headache, paroxysmal headache with gaze paresis, postural syncope, loss of consciousness, and sudden death. A 30-year-old woman with no specific medical history except chronic headache was found collapsed in a public toilet per se. Postmortem examination revealed no external injuries or internal diseases except a cystic lesion of the pineal gland. Histologic examination showed an internal cyst surrounded by glial tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…Untreated, the potential exists for catastrophic obstructive hydrocephalus, although evidence from case reports remains suggestive rather than definitive. 15-17…”
Section: Discussionmentioning
confidence: 99%
“…Untreated, the potential exists for catastrophic obstructive hydrocephalus, although evidence from case reports remains suggestive rather than definitive. 15-17…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system benign tumors other than CPP can cause fatality (Barranco et al 2018). Despite the rarity of these cases, Milroy and Smith (1996) and Na et al (2014) reported several cases where pineal gland cysts, which are benign tumors, caused compression and sudden unexpected deaths. Although in these reports a contributing factor such as an intense effort was responsible for an increase in intracranial pressure and cerebral perfusion and thus death, in our case, we do not know exactly if the deceased had an intense physical effort or any other contributing factor before his death.…”
Section: Discussionmentioning
confidence: 99%
“…Сужение венозных сосудов может вызывать нарастающее давление в венах и, как следствие, интерстициальный отек мозгового вещества [54]. По данным других исследований [9,11,13], причина головной боли заключается в закрытии кистой входа в водопровод мозга, как это бывает при коллоидных кистах, либо кровоизлиянии в КШТ.…”
Section: головная больunclassified
“…Почти у половины (44%) пациентов, оперированных по поводу КШТ, имелась гидроцефалия, которая в 33% случаев была вызвана кровоизлиянием в кисту. Помимо этого, в литературе описаны случаи синкопальных состояний и случаи внезапной смерти, связанные с внезапным закрытием кистой входа в сильвиев водопровод [8,9,[11][12][13].…”
Section: гидроцефалия и внутричерепная гипертензияunclassified